Criterion validity of a field-based assessment of aerobic Capacity in wheelchair rugby athletes - Goosey-Tolfrey, V. L.; de Groot, S.; Tolfrey, K.; Paulson, T. A. W. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To confirm whether peak aerobic capacity determined during laboratory testing could be replicated during an on-court field-based test in wheelchair rugby players.